(untitled) (Indian Journal of Child Health, 2015)
Background: Epidemiologists and social scientists have devoted increasing attention to studying care seeking behavior associated with two leading causes of death namely acute respiratory infections and diarrhea. Objective: This study was planned to assess and compare the health care seeking behavior of urban and rural population in two districts, one with better and other with poor health parameters. Materials and Methods: A cross-sectional study was planned in the state of Uttarakhand to assess the differences in care seeking behavior in its urban and rural population. Data were collected from two districts namely Dehradun and Uttarkashi. Mothers (140) having children up to 5 years of age were interviewed in both the districts and questionnaire was administered to evaluate the care seeking behavior among mothers. Results: Children <1 year and more than 3 years were reported to fall ill more than children between 1 and 3 years in both Dehradun and Uttarakashi, with fever, cough, cold, diarrhea and vomiting, and pneumonia as the most common reported diseases. The average number of symptoms care seeking pattern and hospital treatment was higher in Dehradun despite a similar level of education of mothers in both the regions. Conclusion: Dehradun, having better health facilities, could address the concerns in health of children.